The regulatory role of metabolic organ-secreted factors in the nonalcoholic fatty liver disease and cardiovascular disease - Qin, Li; Wu, Junru; Sun, Xuejing; Huang, Xuewei; Huang, Wei; Weng, Chunyan; Cai, Jingjing (Frontiers in Cardiovascular Medicine, 2023)
Nonalcoholic fatty liver disease (NAFLD) is a chronic metabolic disease characterized by an excessive accumulation of fat in the liver, which is becoming a major global health problem, affecting about a quarter of the population. In the past decade, mounting studies have found that 25%-40% of NAFLD patients have cardiovascular disease (CVD), and CVD is one of the leading causes of death in these subjects. However, it has not attracted enough awareness and emphasis from clinicians, and the underlying mechanisms of CVD in NAFLD patients remain unclear. Available research reveals that inflammation, insulin resistance, oxidative stress, and glucose and lipid metabolism disorders play indispensable roles in the pathogenesis of CVD in NAFLD. Notably, emerging evidence indicates that metabolic organ-secreted factors, including hepatokines, adipokines, cytokines, extracellular vesicles, and gut-derived factors, are also involved in the occurrence and development of metabolic disease and CVD. Nevertheless, few studies have focused on the role of metabolic organ-secreted factors in NAFLD and CVD. Therefore, in this review, we summarize the relationship between metabolic organ-secreted factors and NAFLD as well as CVD, which is beneficial for clinicians to comprehensive and detailed understanding of the association between both diseases and strengthen management to improve adverse cardiovascular prognosis and survival.